Endotracheal Tube Cuff Pressure Monitoring in Children - V. V. Lazarev; E. M. Kopteva; L. E. Tsypin; I. G. Khamin; D. V. Dorokhov (Общая реаниматология)
Objective: to estimate tracheal morphological changes in children, by using a device for the continuous monitoring and regulation of endotracheal tube cuff pressure. Subjects and methods. Two groups of children were examined. In Group A comprising 22 children aged 2 months to 16 years, the adequacy of the external control balloon palpation method was estimated to measure endotracheal tube cuff pressure. In Group B consisting of 12 children aged 5 to 18 years on mechanical ventilation for more than 3 days, the efficiency and appropriateness of applying a PressureEasy device for monitoring the pressure in the endotracheal tube cuff were assessed to prevent postintubation tracheal complications. In the latter group, the authors identified a study subgroup (BI) of 8 patients where this device was employed and a control group of 4 patients (BII) where it was not used. Results. Group A showed that endotracheal tube cuff pressure was 20—30 cm H2O in 31.8% of cases, greater than 30 cm H2O in 36.4%, and lower than 20 cm H2O in 31.8%. Subgroup BI displayed considerably lower macro- and microscopic histological changes than Subgroup BII. Conclusion. Determination of endotracheal tube cuff pressure by palpation of the external control balloon does not reflect its real values. The magnitude of tracheal changes is more intensive if continuous monitoring and regulation of pressure in the endotracheal tube cuff is absent. The PressureEasy device to monitor endotracheal tube cuff pressure permits its variability maintenance at a given level, by mitigating the damaging effect of the cuff on tracheal tissue. Key words: endotracheal tube, cuff, histology, ischemia, prevention, pressure, trachea.